A "Turn‐On" Fluorescence Probe for Selective Detection of Al3+ in Aqueous Environment: Crystal Structure, Theoretical and Cell Imaging Studies. Issue 7 (17th February 2020) - Rani Gupta, Shraddha; Yadav, Pranjalee; Singh, Priya; Koch, Biplob; Singh, Vinod P.
Abstract: A furan‐based water soluble fluorescent probe (E)‐N′‐(2, 4‐dihydroxybenzylidene)furan‐2‐carbohydrazide (DBF) has been synthesized and characterized by 1 H NMR, 13 C NMR, ESI‐mass spectroscopy and single crystal X‐ray diffraction techniques. The synthesized probe exhibits a "turn‐on" fluorescence response towards Al 3+ in Tris‐HCl buffer (10 mM) with no significant interference from other metal ions. The strong fluorescence in the presence of Al 3+ is attributed to the CHEF (chelation enhanced fluorescence), inhibition of PET (photo‐induced electron transfer) and C=N isomerization. 1 : 1 stoichiometric ratio between DBF and Al 3+ was rationalized by Job's plot. Binding constant and LOD were calculated to be 1.031×10 5  M −1 and 6.34×10 −8  M, respectively. MTT assay on live A549 cells indicated no serious cytotoxicity in the cells even at higher concentration. Further, DBF was successfully used for the detection of accumulated Al 3+ in the cytoplasm of cells. Abstract : (E)‐N′‐(2, 4‐dihydroxybenzylidene)furan‐2‐carbohydrazide (DBF) has been synthesized and characterized. DBF acts as highly selective fluorescent sensor for Al 3+ over other cations. The binding constant (KB ) and detection limit for Al 3+ are determined. It has been utilized in intracellular detection of Al 3+ ions.